A cross-sectional online survey on oncologists’ attitudes toward and experiences with providing patients with audio recordings of their medical encounters - Cheyenne Topf; Pola Hahlweg; Isabelle Scholl (Scientific Reports)
Abstract Providing patients with audio recordings of their medical encounters, termed consultation recordings, has shown promising benefits, especially for patients with cancer. While patients favor these recordings, international research indicated that physicians have mixed feelings. To date, research specific to Germany remains limited. This study investigated German oncologists’ attitudes and experiences through a nationwide cross-sectional quantitative online survey, informed by semi-structured interviews. Attitudes, prior experiences and desire for consultation recordings were assessed. Data was analyzed using descriptive statistics and subgroup analyses. Ninety-four physicians participated, with about half expressing a generally positive attitude, though overall attitudes were mixed. Expected benefits included improved patient recall and communication, while concerns centered around potential misuse of recordings, data confidentiality, and increased legal risks. Experiences were limited, with 12% reporting previous use. Fourteen percent expressed a willingness to offer recordings in future and 31% were undecided. This study highlights cautious openness among German oncologists, tempered by concerns over data security and legal implications, which may hinder adoption. This could be addressed by providing sound evidence regarding benefits and concerns, and enabling positive experiences. Further research should include feasibility testing in routine cancer care and re-evaluation of these results in representative samples and other specialties.